The book of lost names [compact disc, unabridged] - Harmel, Kristin (Simon & Schuster Audio, 2020)
As a graduate student in 1942, Eva was forced to flee Paris after the arrest of her father, a Polish Jew. Finding refuge in a small mountain town in the Free Zone, she begins forging identity documents for Jewish children fleeing to neutral Switzerland. But erasing people comes with a price, and Eva decides she must find a way to preserve the real names of the children who are too young to remember who they really are. Sixty-five years later, a book is discovered that appears to contain some sort of code, but researchers don't know where it came from, or what the code means. Only Eva holds the answer, but will she have the strength to revisit old memories and help reunite those lost during the war?